Lipid droplet biogenesis: a mystery “unmixing”? - Renne, MF; Klug, YA; Carvalho, P (Elsevier, 2020)
Lipid droplets (LDs) are versatile organelles with central roles in lipid and energy metabolism in all eukaryotes. They primarily buffer excess fatty acids by storing them as neutral lipids, mainly triglycerides and steryl esters. The neutral lipids form a core, surrounded by a unique phospholipid monolayer coated with a defined set of proteins. Thus, the architecture of LDs sets them apart from all other membrane-bound organelles. The origin of LDs remained controversial for a long time. However, it has become clear that their biogenesis occurs at the endoplasmic reticulum (ER) and is a lipid driven process. LD formation is intiatied by the demixing of neutral lipids from membrane phospholipids, leading to the formation of a neutral lipid “lens” like structure between the leaflets of the ER bilayer. As this lens grows, it buds out of the membrane towards the cytosol to give rise to a LD. Recent biophysical and cell biological experiments indicate that LD biogenesis occurs at specific ER domains. These domains are enriched in various proteins required for normal LD formation and possibly have a lipid composition distinct from the remaining ER membrane. Here, we describe the prevailing model for LD formation and discuss recent insights on how proteins organize ER domains involved in LD biogenesis.